PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN BUDAYA ORGANISASI TERHADAP KINERJA MANAJERIAL PADA PT PERKEBUNAN NUSANTARA VIII - Lili Dahliani; Rifa Rusiva; Rahmat Saleh (Jurnal Bisnis Terapan, 2021)
PT Perkebunan Nusantara VIII is a state-owned plantation engaged in the Agribusiness and Agro-Industry sectors.. The budget preparation process that involves subordinates can improve the performance of subordinates in achieving budget targets. Participatory budgets can be carried out to achieve budget targets by negotiating between superiors and subordinates. In addition to being measured by employees and the cultural linkages attached to them, organizational success can also be seen from the overall performance of the organization. The purpose of this study was to examine the effect of budgetary participation and organizational culture on managerial performance. The total population of this study was 23 PTPN VIII tea gardens in West Java. Respondents in this study were garden managers, assistant heads, assistants, and large foremen of PTPN VIII (Persero) who were involved in the participation process (proposing and or implementing) the budget with a total sample of 63 respondents selected through purposive sampling. testing the quality of the data used is the validity and reliability of the data. The classical assumptions used are normality test, multicollinearity, and heteroscedasticity test. Model analysis uses multiple linear regression is used to analyze data with the help of the SPSS.23.0 program. The results showed that budget participation had a significant effect on managerial performance and organizational culture had a significant effect on managerial performance.